Federal Policymaking and the Poor : National Goals, Local Choices, and Distributional Outcomes. - Rich, Michael J. (Princeton legacy library., 2014)
Do federal, state, and local governments differ in their responsiveness to the needs of the poorest citizens? Are policy outcomes different when federal officials have greater influence regarding the use of federal program funds? To answer such questions, Michael Rich examines to what extent benefits of federal programs actually reach needy people, focusing on the relationship between federal decision-making systems and the distributional impacts of public policies. His extensive analysis of the Community Development Block Grant Program (CDBG), the principal federal program for aiding citie.